The Deregulation of natural gas - Mitchell, Edward J.; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1983)
The papers in this volume represent the state of the debate at the time of the Conference. The Conference papers provide background information and analysis that will make a contribution to the legislative debate over deregulation.
"A conference sponsored by the American Enterprise Institute for Policy Research"--Cover.
Includes bibliographical references.
rpm 25/01/2019
Loans
Keywords: Natural gas